2021
DOI: 10.1371/journal.pone.0248868
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of extubation outcome in mechanically ventilated patients: Development and validation of the Extubation Predictive Score (ExPreS)

Abstract: Despite the best efforts of intensive care units (ICUs) professionals, the extubation failure rates in mechanically ventilated patients remain in the range of 5%–30%. Extubation failure is associated with increased risk of death and longer ICU stay. This study aimed to identify respiratory and non-respiratory parameters predictive of extubation outcome, and to use these predictors to develop and validate an “Extubation Predictive Score (ExPreS)” that could be used to predict likelihood of extubation success in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 39 publications
4
27
2
2
Order By: Relevance
“…The predictive performance decreases in patients with multi-organ dysfunction, older age, prolonged MV, and severe illness [26][27][28][29][30][31]. The lack of reliable weaning parameters is related to the heterogeneity of critically ill patients and their ever-changing clinical courses [32][33][34][35]. The causes of weaning failure are not exclusively attributable to oxygenation or ventilation insufficiency; cardiac function, volume status, muscle deconditioning, and the presence of delirium also affect weaning outcomes [9,23,[36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…The predictive performance decreases in patients with multi-organ dysfunction, older age, prolonged MV, and severe illness [26][27][28][29][30][31]. The lack of reliable weaning parameters is related to the heterogeneity of critically ill patients and their ever-changing clinical courses [32][33][34][35]. The causes of weaning failure are not exclusively attributable to oxygenation or ventilation insufficiency; cardiac function, volume status, muscle deconditioning, and the presence of delirium also affect weaning outcomes [9,23,[36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Patients who tolerated the SBT for 30 min and presented a rapid shallow breath index (RSBI) < 105 breaths/min/L were extubated. 14 Inclusion, exclusion, weaning, and extubation criteria were defined based on a previously published study, 12 except for the inclusion of the COVID-19 diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…The Fisher Exact test was used to evaluate the association of extubation outcome at 48 h and during ICU stay in this cohort compared to the cohort of our previous published study. 12 The p-values were also presented considering a significance level of 5%. A post hoc power analysis yielded a statistical power of 0.96 (p2 = 0.78; p1 = 0.12; n = 77, α = 0.05 – Gpower 3.1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies have shown that there are still 10% to 20% of patients who pass the SBT test and fail the extubation [3,4]. Extubation failure will cause incalculable physical and psychological harm to patients, and increase mortality and medical costs [5][6][7]. Therefore, reducing the extubation failure is vital to the prognosis of MV patients.…”
Section: Introductionmentioning
confidence: 99%